2014
DOI: 10.1210/jc.2014-2042
|View full text |Cite
|
Sign up to set email alerts
|

Serum Sclerostin and Adverse Outcomes in Nondialyzed Chronic Kidney Disease Patients

Abstract: This is the first study that shows that serum sclerostin values are associated, even after multiple adjustments, with fatal and nonfatal CVEs in a nondialyzed CKD population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 38 publications
10
76
1
1
Order By: Relevance
“…Interestingly, we found sclerostin levels in hemodialysis patients to be considerably higher than in the control group, which is in line with previous results [15,16,24].This phenomenon could be explained not only by reduced clearance in impaired kidney function, but also by an enhanced production in uremia. Cejka et al were the first to document increased renal sclerostin elimination with declining kidney function suggesting an increased sclerostin production in uremia [22] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, we found sclerostin levels in hemodialysis patients to be considerably higher than in the control group, which is in line with previous results [15,16,24].This phenomenon could be explained not only by reduced clearance in impaired kidney function, but also by an enhanced production in uremia. Cejka et al were the first to document increased renal sclerostin elimination with declining kidney function suggesting an increased sclerostin production in uremia [22] .…”
Section: Discussionsupporting
confidence: 92%
“…A study by Viaene et al found a trend towards survival benefit with higher circulating sclerostin levels in 100 hemodialysis patients after a median follow-up time of 637 days [15], suggesting that sclerostin might be a calcification inhibitor. In contrast, Kanbay et al found higher sclerostin values to be associated with fatal and non-fatal cardiovascular events in 173 non-dialyzed patients with CKD stages 3-5 after a mean follow-up of 26 months [16]. A very recent study by Drechsler et al found high sclerostin levels to be protective for cardiovascular mortality in 673 incident dialysis patients [17].…”
Section: Sclerostin In Controls Versus Hemodialysis Patientsmentioning
confidence: 95%
“…63,64 As with subjects having normal renal function, higher concentrations of sclerostin occurs in men, which can be explained by a higher bone mass and indirectly a greater number of osteocytes. 65 The relationship between the concentration of phosphorus and sclerostin (independent from GFR) indicates its potential contribution to the regulation of its secretion by osteocytes. 66 Ishimura et al showed that serum sclerostin was significantly and independently associated with BMD.…”
Section: Sclerostin In Chronic Kidney Diseasementioning
confidence: 99%
“…In particular, serum sclerostin was described in patients with chronic kidney disease and uremic patients, underlying its high levels, closely related to mortality risk. 8 The aim of this study was to evaluate the role of serum sclerostin in uremic patients, analyzing its behavior during a single hemodialysis session, through Acetate Free Bio-filtration (AFB) and high-efficiency convective technique. Moreover, we investigated the possible correlations between serum levels of sclerostin and different markers of uremic osteodystrophy and vascular calcification.…”
Section: Introductionmentioning
confidence: 99%